Depth of invasion alone as a prognostic factor in low‐risk early‐stage oral cavity carcinoma. (2nd January 2019) - Kozak, Margaret M.; Shah, Jennifer; Chen, Michelle; Schaberg, Kurt; von Eyben, Rie; Chen, Jie Jane; Bui, Timothy; Kong, Christina; Kaplan, Michael; Divi, Vasu; Hara, Wendy
Abstract : Objectives: To evaluate the significance of increasing depth of invasion (DOI) as the sole risk factor for recurrence in patients with low‐risk early‐stage oral cavity squamous cell carcinoma (OCSCC). Methods: We retrospectively reviewed 560 patients with OCSCC treated at our institution between 2003 and 2013. Patients were included if they had low‐risk early‐stage OCSCC treated with surgical resection ± neck dissection and no adjuvant therapy. Low risk was defined as absence of positive or close margins, lymphovascular invasion, perineural invasion, and positive lymph nodes. Patients with tumor (T)3‐T4 disease were excluded. Pathology specimens were independently re‐reviewed by two board‐certified pathologists to confirm proper measurement of DOI. Kaplan‐Meier and Cox proportional hazards regression analyses were performed to identify factors predictive for recurrence as well as progression‐free survival (PFS) and overall survival (OS). Results: A total of 126 patients with low‐risk early‐stage T1‐2N0 OCSCC were included. Median follow‐up time was 42.5 months and median DOI was 4 mm. There was no significant difference in incidence of local ( P = 0.95), regional ( P = 0.81), or distant recurrence ( P = 0.96) among patients with DOI < 4 mm versus ≥4 mm. On multivariable analysis, DOI was significant for both PFS ( P = 0.03) and OS ( P = 0.002). Conclusion: In this study, we show that in the absence of other high‐risk pathologic features, DOI ≥ 4 mm does not portend for increased incidence of local, regional, or distant relapse in patients treated with surgery alone; however, increasing DOI is a marker for worse PFS and OS in patients with low‐risk, early‐stage OCSCC. Level of Evidence: 4 Laryngoscope, 129:2082–2086, 2019